Pelatihan Penulisan Artikel Ilmiah bagi Mahasiswa Pendidikan Biologi FPMIPA IKIP Mataram - Septiana Dwi Utami; Sri Nopita Primawati; Herdiyana Fitriani; Baiq Muli Harisanti; Ida Royani (Jurnal Pengabdian UNDIKMA, 2020)
The objectives of this service activity are: (1) increasing student knowledge about the ins and outs of writing scientific papers and scientific articles , and (2) improving the ability to write scientific articles among students of Biology Education FSTT Undikma Mataram. Community service activities were carried out for 2 days, with 3 stages of activities, namely: (1) Introduction, (2) core activities, and (3) workshops. The partner in this service activity is the Biology Education Study Program of FSTT UNDIKMA Mataram, especially for students who have taken thesis examinations and will compile articles based on their research findings. From the results of the evaluation of the activities, it can be concluded that the purpose of this service activity has been achieved according to expectations, namely increasing student knowledge about the ins and outs of writing scientific papers and scientific articles, the achievement can be seen from the results of student articles that have been presented through the presentation of the results of the preparation of their articles showing that the results are very good and in line with expectations.